Računalniška dinamika tekočin v farmacevtski industriji - Šibanc, Rok (Farmacevtski vestnik, 2011)
Computational fluid dynamics (CFD) uses numerical methods and physical models to solve and analyze different problems that involve fluid flow, heat transfer, mass transfer and chemical reaction. CFD modeling is used to optimize different process parameters, increase understanding of the process and get information about different process values that otherwise could not be measured or are hard to measure.
Keywords: farmacevtska industrija; mešalniki; mešanje; modeli; računalniška dinamika tekočin; tok tekočin